PENINGKATAN HASIL BELAJAR KOGNITIF BIOLOGI SISWA MELALUI PEMBELAJARAN PREDICT-OBSERVE-EXPLAIN (POE) DI SMAN 4 KOTA BENGKULU - Yansyah, Rekhawita Putri; Nopriyeni, Nopriyeni (JURNAL PERSPEKTIF PENDIDIKAN, 2022)
This study aims to determine the effect on the application of the Predict-Observe-Explain (POE) Learning Model to Improve Student Biology Cognitive Learning Outcomes. This research was carried out at SMA Negeri 4 Bengkulu City in January-February 2022, with the population being all class X MIPA SMA Negeri 4 Bengkulu City and the samples were class X MIPA 2 (Experimental Class) and Class X MIPA 5 (Control Class). Samples were taken using the Cluster Random Sampling technique with an experimental type of research design, namely prettest-posttest group design. With the technique of collecting data through tests, namely in the form of questions in the form of Essays totaling 5 questions. Cognitive learning outcomes data obtained from the calculation of prerequisite tests in the form of normality test and homogeneity test. After testing the prerequisites, then testing the results of data analysis using the T test, namely the Independent Samples t-Test. And the results of data analysis show that the application of the POE learning model can improve the achievement of students' basic competencies at SMA Negeri 4 Bengkulu City. The results of the Independent Samples t-Test (t) of 8.410 with a p value of 0.000. Because the value of p <0.05, it is said that there is an influence between the learning outcomes of the experimental class and the learning outcomes of the control class. Thus it can be said that the application of the Predict-Observe-Explain (POE) learning model has a significant effect on improving the cognitive learning outcomes of Biology Students at SMA Negeri 4 Bengkulu City.